2003
DOI: 10.1159/000070096
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Increases Expression of the Calcium-Binding Protein S100P in Human Gastric Cancer Cells

Abstract: Retinoids mediate a wide spectrum of antitumor activities through induction of growth arrest, differentiation or apoptosis. To determine whether the effects of retinoids are mediated by specific gene activation or repression, one-day treatments of SC-M1 CL23 gastric cancer cells with vehicle alone or all-trans retinoic acid (tRA) (10 µM) were compared using differential display analysis. A 432-bp cDNA fragment from the tRA-treated cells was differentially amplified and its sequence analysis indicated homology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
5
0
2
Order By: Relevance
“…However, S100P, as a marker of growth, metastasis and invasion in other tumors, was significantly downregulated in GC cases in our study. Decreased S100P expression was reported to be closely associated with early events in the terminal differentiation of human esophageal epithelial cells (Sato and Hitomi 2002) which likely modulates activity of the β-catenin-Tcf signal pathway via regulation of β-catenin degradation (Shyu et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, S100P, as a marker of growth, metastasis and invasion in other tumors, was significantly downregulated in GC cases in our study. Decreased S100P expression was reported to be closely associated with early events in the terminal differentiation of human esophageal epithelial cells (Sato and Hitomi 2002) which likely modulates activity of the β-catenin-Tcf signal pathway via regulation of β-catenin degradation (Shyu et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that MUC5AC may not always detect IPMN. Other antibodies, such as the pancytokeratin antibody (AE1/AE3), CAM5.2, and cytokeratins 8,18,and 19), are also expressed in all IPMNs. However, these proteins are epithelial markers that are also found in normal ducts of the pancreas [14].…”
Section: Discussionmentioning
confidence: 99%
“…There have thus been no reports on diagnostic markers to distinguish all types of IPMNs from nonneoplastic lesions [14]. S100P, a small protein composed of 95 amino acids, is a member of the S100 protein family and is detected in several solid tumors including pancreatic cancer [15][16][17][18][19][20]. In pancreatic cancer, its expression was regulated by DNA hypomethylation [21], and S100P expression is associated with aggressiveness, such as cell proliferation [22].…”
Section: Introductionmentioning
confidence: 99%
“…Only S 100P was found to be expressed in SGC7901 and SGC7901/ADR cells. It was recently reported that S 100P was significantly upregulated in gastric cancer cells treated with retinoic acid [27], which suggested a potential role of S 100P in retinoic acid resistance. In the present study, however, there was no obvious difference in S 100P expression among the six cell lines tested (SGC7901 and SGC7901/ADR and their transfectants).…”
Section: Discussionmentioning
confidence: 96%